Memoirs of Louis XIV and His Court and of the Regency $1 (BVolume 10s - Saint-Simon, Louis de Rouvroy, duc de, 1675-1755 (Salt Lake City, UT : Project Gutenberg, 2004)
"Memoirs of Louis XIV and His Court and of the Regency $1 (BVolume 10" by the Duke of Saint-Simon is a historical account likely written during the early 18th century. This volume focuses on the twilight years of King Louis XIV$1 (Bs reign and the ensuing regency period, exploring the political intrigues, personal characteristics, and social dynamics surrounding the king and his court. It aims to provide insights into the final days of Louis XIV, examining the interplay of key figures, particularly M. le Duc d'Orleans, as they grapple with the impending shift in power following the King's death. The beginning of this volume sets the stage by discussing the waning health of Louis XIV and the critical decisions made during his final days. It introduces M. le Duc d'Orleans as a central player, detailing his personality traits$1 (Bfrom his amiable demeanor to his personal struggles with ambition and debauchery. The opening provides a glimpse into the tensions within the court, as M. d'Orleans navigates the machinations of those around him, including Madame de Maintenon and other influential figures. Additionally, the narrative hints at the transition of power that is about to unfold, foregrounding the significance of the coming regency and the conflicts that will arise from it. (This is an automatically generated summary.)s
Release date is 2004-12-03
Produced by David Widger
Keywords: France -- Court and courtiers; France -- History -- Louis XIV, 1643-1715; France -- History -- Regency, 1715-1723